DIGITAL GOVERNANCE DALAM APLIKASI CIBINONG GANCANG NGUBARAN DULUR (CAGEUR) DI RUMAH SAKIT UMUM DAERAH (RSUD) CIBINONG KABUPATEN BOGOR - Daffa Diysa Fauzian; Sri Suwitri (Journal of Management and Public Policy, 2026)
Limited access to healthcare services, unequal distribution of health workers, and increasing public demand for fast and efficient services remain major challenges in the delivery of public healthcare. The utilization of digital technology through the concept of digital governance has become a strategic approach to address these issues. This study aims to analyze the implementation of the Cibinong Gancang Ngubaran Dulur (Cageur) Application as a digital health service innovation at Cibinong Regional General Hospital (RSUD Cibinong), Bogor Regency. This research employs a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving application managers, healthcare workers, and service users. The analysis focuses on three dimensions of digital governance: digital strategy, digital policy, and digital standards, particularly in telemedicine, home care, and digital referral services. The findings indicate that the Cageur Application has contributed positively to improving access and efficiency of healthcare services, especially in home care and digital referral services. However, the utilization of telemedicine services remains suboptimal due to limited socialization, patients’ preference for face-to-face consultations, and technical as well as human resource constraints. This study concludes that the implementation of the Cageur Application has been relatively effective in supporting digital-based healthcare governance, yet further improvements are needed through strengthened socialization strategies, increased digital literacy among the community, and optimization of resources to ensure more effective and sustainable digital governance.